Ambiguity in Writing Story Text of Experience of Grade IV Students of the Champion School Denpasar-Bali - Bonefantura Anggur (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2019)
This research aims is to describe the lexical ambiguity, gramatical ambiguity and what factors that influence the writing skills of primary IV students of The Champion Denpasar-Bali. The method of this research is a qualitative approach. The data is obtained by the written story text from the student’s experience. The results showed that the type of ambiguity contained is consisted of lexical ambiguity and grammatical ambiguity. Lexical ambiguity is divided into two parts, namely polysemy and homonymy, while grammatical ambiguity is divided into four parts including: grammatical ambiguity caused by grammatical word formation events, grammatical ambiguity in similar phrases, grammatical vocabulary because of sentence context or lack of grammatical context and ambiguity because of the inaccuracy of the grammatical structure. The factors that influence the writing skills of primary IV students of The Champion Denpasar - Bali. First, the use of a foreign language (English) as a daily communication language of students in schools that intervene in Indonesian, which causes the lack of vocabulary that students have so that students find it difficult to write the text of the Indonesian experience stories correctly. Second, family, the assumption that the task of giving lessons to students is only the duty of the teacher to make the family environment rarely train their children to write at home. Third is, intelligence which is related to students' ability to absorb the material taught to them. The fourth is interest related to encouragement, motives, and emotional responses.